The Formats of Julia Sets for Complex Dynamic Systems (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, the formats of Julia sets for a class of nonlinearcomplex dynamic systems with variable coefficients were studied under certainconditions. For the complex dynamic systems in piecewise cases, we proposedsome methods to control the forms of their Julia sets and stable domainsanalytically. What's more, we illustrated that our methods worked well bycomputational simulations. Our work provides a better understanding abouthow to control the Julia sets of certain complex dynamic systems.